The outcome of conservative treatment of adult distal radius fractures compared with the other wrist: radiological and functional evaluation. Issue 3 (2014) - Uslu, Mustafa; Arıcan, Mehmet; Işık, Cengiz; Sarman, Hakan; Boyraz, İsmail
No abstract available